Two-step heating mode with the same energy consumption as conventional heating for enhancing methane production during anaerobic digestion of swine wastewater. (1st March 2018) - Liu, Yi; Ma, Shichun; Huang, Liang; Wang, Shiyu; Liu, Gangjin; Yang, Hongnan; Zheng, Dan; Cheng, Jingsi; Xu, Ze; Deng, Liangwei
Abstract: With high percentage of washing water, swine wastewater is characterized by large volume and low concentration of total solids. Thus, in treating swine wastewater, it is relatively difficult to heat digesters, resulting in low methane production at low ambient temperatures (ATs). To increase methane production from swine wastewater, this study proposed a novel "two-step heating (TSH)" mode with the same energy consumption as a one-step process for anaerobic digestion. Compared with the traditionally heated digesters (one-step heating), the digestion temperature in TSH digesters increased by 3.50–10.50 °C under the assumption of no heat dissipation and by 3.30–9.25 °C in the actual experiments. Although methane production of the TSH digesters improved by 15% in our experiments, the improvement was far less than theoretically estimated. This was mainly caused by short hydraulic retention time and sludge washout in the digesters. Moreover, the acetoclastic methanogenesis, accomplished by genus Methanosaeta, was the major methanogenesis pathway at low temperatures in both the TSH and conventional heating modes. However, the relative abundance of syntrophic bacteria and hydrogenotrophic methanogens in TSH mode were both higher than in the digesters operation in conventional heating mode when the atmospheric temperature was below 10 °C. Highlights: A two-step heating mode for anaerobic digestion of swine wastewater was developed. Digestive temperature of digesters in two-step heating mode could be increased. Methane production of digesters in two-step heating mode increased by up to 15%. The syntrophic oxidation in the digesters in two-step heating mode was more active.